The Effect of Photovoltaic Panels on the Rooftop Temperature in the EnergyPlus Simulation Environment - Changhai Peng; Jianqiang Yang (International Journal of Photoenergy)
In this paper, the effects that photovoltaic (PV) panels have on the rooftop temperature in the EnergyPlus simulation environment were investigated for the following cases: with and without PV panels, with and without exposure to sunlight, and using roof materials with different thermal conductivities and for different climatic zones. The results demonstrate that heat transfer by convection, radiation, and conduction in the air gaps between PV panels and the building envelope can be simulated in the EnergyPlus environment when these air gaps are in the “air conditioning zone.” Nevertheless, in most cases, particularly on the rooftop, the air gaps between the PV panels and the building envelope cannot be set as the “air conditioning zone.” Therefore, in this case, none of the EnergyPlus models are appropriate to simulate the effect that PV panels have on the rooftop temperature. However, all the terms of the Heat Balance Model, including the absorbed direct and diffuse solar radiation, net long-wave radiation with the air and surroundings, convective exchange with the outside air, and conduction flux in or out of the surface, can still be used to calculate the temperature and heat flux within the BIPV’s air gap.